(untitled) (Képzés és Gyakorlat : Neveléstudományi folyóirat, 2007)
Sports play a key role in maintaining one’s health, bringing about completeness and improves one physically and psychologically. This approach in attitude is useful in higher education also. Every Branch in the Western Hungarian Colleges teach physical education, but there are some faculty departments where course specific athletic training lessons are practiced. These courses are Teaching, Kindergarten Teaching, and Social Education training. The Elek Benedek Faculty Department of Social Pedagogy employs to its advantage fundamental theoretical and applied basic constituents which make up the training instruction, where the students receive not only educational support in order that they may survey their own fitness level and development, but in addition they are also given the learning tools to exploit in exploring health developments and athletic maturation possibilities. The presently selected physical education topics (Sport recreation, Leisure time sports theory and practice I and II) have been worked up in a digital format, consisting of e-leaming materials, in order that the supervision of the education level and effectiveness might be enhanced.